Scoping review about the professional integration of internationally educated health professionals. Issue 1 (December 2016) - Covell, Christine; Neiterman, Elena; Bourgeault, Ivy
Abstract Background Over the last decade, Canada has been one of the top destination countries for internationally educated health professionals (IEHPs). After arrival, many struggle to professionally recertify and secure employment in their field. Considerable funding has been allocated to the development of new policies and programs to facilitate IEHPs' professional integration. Literature about the professional integration process and the available policies and programs is abundant, not synthesized and dispersed among a wide range of health professions and the academic and grey literature. This, in combination with the sustained policy relevance, contributed to the timeliness and necessity for conducting this scoping review. Methods We used an updated version of Arskey and O'Malley's six-stage scoping review framework to summarize the amount, types, sources and distribution of the literature. Findings were summarized numerically and thematically. The themes included pre-immigration activities and programs, early arrival activities and programs, professional recertification and workplace integration. Results Four hundred and seven published sources from 2000–2012 were retained for data charting and extraction. Most focused on international medical graduates or internationally educated nurses. IEHPs from the allied health professions were underrepresented. Methodologically, about one quarter of the papers are empirical studies with the next largest category being reports from professional certification bodies and educational institutions. The overarching concern is with workplace integration, professional recognition and bridging programs. Nursing dominates the literature about pre-immigration activities and programs whereas the literature about early arrival activities and programs, professional recertification and workplace integration is dominated by medicine. Although the literature does contain some information for IEHPs in the allied health professions, the thematic analysis did not identify a clear trend. A notable increase in the number of publications was present. Conclusions The literature about IEHPs' professional integration in Canada is abundant. This reflects the sustained policy relevance of the recruitment, recognition and professional integration for IEHPs in Canada. This demonstrates that Canada provides an excellent case for this review from which the findings may have international significance. Nevertheless, little information is available about the effectiveness of the policies and programs available to facilitate IEHP integration, an area that requires further consideration.